The utility of transcutaneous carbon dioxide measurements in the emergency department: A prospective cohort study - Mitchell Barneck; Linda Papa; Ashley Cozart; Kain Lentine; Jay Ladde; Linh Nguyen; Jeremy Mayfield; Josef Thundiyil (Journal of the American College of Emergency Physicians Open)
Abstract Background Rapid identification of patients with occult injury and illness in the emergency department can be difficult. Transcutaneous carbon dioxide (TCO2) and oxygen (TO2) measurements may be non‐invasive surrogate markers for the identification of such patients. Objectives To determine if TCO2 or TO2 are useful adjuncts for identifying severe illness and the correlation between TCO2, lactate, and end tidal carbon dioxide (ETCO2). Methods Prospective TCO2 and TO2 measurements at a tertiary level 1 trauma center were obtained using a transcutaneous sensor on 300 adult patients. Severe illness was defined as death, intensive care unit (ICU) admission, bilevel positive airway pressure, vasopressor use, or length of stay >2 days. TCO2 and TO2 were compared to illness severity using t tests and correlation coefficients. Results Mean TO2 did not differ between severe illness (58.9, 95% CI 54.9–62.9) and non‐severe illness (58.0, 95% CI 54.7–61.1). Mean TCO2 was similar between severe (34.6, 95% CI 33–36.2) vs non‐severe illness (35.9, 95% CI 34.7–37.1). TCO2 was 28.7 (95% CI 24.0–33.4) for ICU vs. 35.9 (95% CI 34.9–36.9) for non‐ICU patients. The mean TCO2 in those with lactate > 2.0 was 29.8 (95% CI 25.8–33.8) compared with 35.7 (95% CI 34.9–36.9) for lactate < 2.0. TCO2 was not correlated with ETCO2 (r = 0.32, 95% CI 0.22–0.42). Conclusion TCO2 could be a useful adjunct for identifying significant injury and illness and patient outcomes in an emergency department (ED) population. TO2 did not predict severe illness. TCO2 and ETCO2 are only moderately correlated, indicating that they are not equivalent and may be useful under different circumstances.